EVALUATION OF GAS SERPIH POTENTIAL IN SANGKAREWANG FORMATION, OMBILIN BASIN - PARULIAN , HOT
Shale gas is a natural gas trapped in fine-grained sedimentary rock (shale formation) that plays a role as source rock in the oil and gas industry. Along with the technology development, gas in shale formation now has a potential to be produced in large quantities. Ombilin Basin has a potential source rock as a producer of hydrocarbons. However, shale potential as a shale gas in the shale play system is still unknown.